Nested polymerase chain reaction with sequence-specific primers typing for HLA-A, -B, and -C alleles: detection of microchimerism in DR-matched individuals - Carter, A S; Cerundolo, L; Bunce, M; Koo, D D; Welsh, K I; Morris, P J; Fuggle, S V (Blood, 1999)
It is widely accepted that donor leukocytes survive within the recipient periphery after blood transfusion or solid organ transplantation. The significance of this microchimerism remains unclear, partially because of the insecurity of assays used to detect the donor-derived material. The techniques used to detect donor-derived DNA within recipient peripheral blood rely largely on major histocompatibility complex class II polymorphism. We and others have shown that the sensitivity of polymerase chain reaction with sequence-specific primers (PCR-SSP) typing for HLA class II alleles can be increased 100-fold by the addition of a primary amplification step (nested PCR-SSP). We have now extended this technique to encompass typing for HLA class I alleles, thereby adding flexibility to microchimerism testing by enabling testing of recipients HLA-DR matched with their donors. However, the high level of sensitivity achieved with the technique (1:100,000) leads to a concomitant decrease in the specificity that results in the amplification of unexpected products, a phenomenon we encountered in the development of our nested PCR-SSP typing system for HLA class II alleles. We describe here how it is possible to compensate for these anomalies by including multiple testing of a pretransfusion sample that acts as a specificity control, establishing a rigorous baseline for subsequent analysis.